Neuron-specific enolase level research in children with COVID-19 - Seriakova, Iryna; Kramarov , Sergiy; Yevtushenko , Vitalii; Kyrytsia , Nataliia; Shadrin , Valerii; Voronov , Oleksandr; Byk , Vitalii; Grynevych, Inna; Zaslavska, Hanna; Zlobynets, Antonina (Bangladesh Journal of Medical Science, 2024)
Introduction COVID-19 is a relevant issue for scientists around the world. Considering the development of numerous complications due to COVID-19, the search for diagnostic approaches for the timely detection of probable lesions of the nervous system is urgent. Objectives was to determine the diagnostic and prognostic value of the NSE marker in children with COVID-19 regarding the complicated course and symptoms of nervous system damage. Materials and methods We conducted a cohort, observational, retrospective study involving 88 children aged 1 month to 18 years with laboratory-confirmed COVID-19 by PCR. Blood serum was collected for the study to assess the level of the neurobiomarker NSE by enzyme immunoassay. We divided patients into two cohorts according to the course of the disease - the main one, which included 42 patients with a complicated course of COVID-19, and a control group - 46 patients with an uncomplicated course of the disease. The study protocol was approved by the Local Ethics Committee of the hospital. Results: In the patients of the control group, NSE was observed at the level of 12.1±1.2 μg/l, while in the children of the main one, the indicator reached 16.9±1.5 μg/l (p=0.087). Increase in the level of NSE above 15 μg/L associated with a significant increase in the risk of the appearance of clinical symptoms of damage to the nervous system and a complicated course in children with COVID-19 (p<0.05). We noted a tendency towards an increase in NSE with increased ESR indicators >10mm/h (p<0.1), a decrease in PTI <85% (p=0,03) and an increase in D-dimer >2.5mg/l (p<0.1). Conclusions We found the diagnostic and prognostic value of the NSE marker in children with COVID-19 regarding the complicated course and symptoms of nervous system damage. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 388-397